Identifying barriers to hepatitis B and delta screening, prevention, and linkage to care among people who use drugs in Philadelphia, Pennsylvania, USA - Beatrice Zovich; Catherine Freeland; Holly Moore; Kara Sapp; Anousha Qureshi; Amy Jessop; Rachel Holbert; Fiona Borondy-Jenkins; Quinn Plunkett; Chari Cohen (Harm Reduction Journal)
Abstract Background People who use drugs (PWUD) are at increased risk for blood-borne viruses, including hepatitis B (HBV) and delta (HDV). Despite the public health threats both viruses present, awareness remains low among at-risk communities and providers who serve them. This study assessed barriers to HBV and HDV prevention, diagnosis, and linkage to care, evaluated existing levels of knowledge, and identified educational needs and preferences among both PWUD and service providers. Methods For this mixed-methods study, data were collected through an anonymous online provider-focused survey, and interviews with PWUD, non-medical staff, and healthcare providers at a harm reduction organization in Philadelphia, PA, USA. Convenience sampling was used for recruitment of both key informants and survey respondents. Survey respondents were categorized according to their type of practice. For the interviews, a codebook was created for qualitative analysis. Data were subsequently organized into thematic categories. Results The top provider-related barriers limiting HBV screening were identified as confusion about insurance coverage (48%) and competing priorities (45%). Barriers to vaccination included patient hesitancy (52%) and challenges with administering multiple doses (39%). Respondents indicated low knowledge of HDV tests (62%) and cited guideline complexity (31%) as barriers to HDV testing. HBV and HDV awareness within the community and among staff was poor. Findings demonstrated that stigma related to drug use and harm reduction posed a significant barrier to care. Participants recommended awareness campaigns tailored for the PWUD community that are non-stigmatizing and non-judgmental, clear, factual, digestible, and interactive, with empowering steps to protect health. Conclusion This study identified major gaps in HBV and HDV service delivery for PWUD, including poor basic knowledge, the need to address this through culturally appropriate, non-stigmatizing and tailored educational programming, and challenges with access to vaccination and testing. Continued initiatives are needed to close disparities, and to continue to provide financial and political support for harm reduction organizations, a frequently cited facilitator of healthcare access for PWUD. Significant efforts are essential to address lack of vaccination, testing, and linkage to care, and to improve health outcomes among PWUD.